2021
DOI: 10.1002/jemt.23889
|View full text |Cite
|
Sign up to set email alerts
|

Micromorphological characters variation of lemma and palea in subtribe of Loliinae (Poaceae)

Abstract: The subtribe Loliinae is one of the largest subtribes of Poeae with about 600 species.Festuca is a large genus with close relations to other genera as Lolium, Castellia, and Vulpia. The taxonomic history of the Festuca-Lolium species group is very complicated. The polyploidy and hybridization make it more confusing. Due to the morphological similarities between genera identification is very difficult, the aim of the present study is to provide the taxonomic characters for the delimitation of the taxa of subtri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The present study described the comparative micromorphological features of 15 Korean irises for the first time. The results of LM and SEM microscopic analysis revealed useful and reliable leaf micromorphological traits of economically important plant families (Choi, Kim, & Jang, 2020b; Gul et al, 2019; Kandemir et al, 2019; Kim et al, 2021; Klimko et al, 2018; Kong & Hong, 2019; Lima et al, 2020; Magauer et al, 2014; Tabaripour et al, 2022). The leaf characteristics of the investigated Korean irises showed great diversity in the leaf margin, epidermal cell outline, stomatal size, and the occurrence of abnormal stomata (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study described the comparative micromorphological features of 15 Korean irises for the first time. The results of LM and SEM microscopic analysis revealed useful and reliable leaf micromorphological traits of economically important plant families (Choi, Kim, & Jang, 2020b; Gul et al, 2019; Kandemir et al, 2019; Kim et al, 2021; Klimko et al, 2018; Kong & Hong, 2019; Lima et al, 2020; Magauer et al, 2014; Tabaripour et al, 2022). The leaf characteristics of the investigated Korean irises showed great diversity in the leaf margin, epidermal cell outline, stomatal size, and the occurrence of abnormal stomata (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on leaf indumentum, including both anatomy and micromorphology, provide important diagnostic criteria for differentiating various plant groups (Asteraceae—Choi, Kim, & Jang, 2020b; Lamiaceae—Gul et al, 2019; Iridaceae—Kandemir et al, 2019; Asparagaceae—Klimko et al, 2018; Colchicaceae—Kim et al, 2021; Polygonaceae—Kong & Hong, 2019; Poaceae—Lima et al, 2020; and Brassicaceae—Magauer et al, 2014). The implications of light and scanning electron microscopy have been widely used to better understand the taxonomic significance of plants (Choi et al, 2020b; Kim et al, 2021; Shahzad et al, 2022; Tabaripour et al, 2022; Ullah et al, 2022). Within the family Iridaceae, various leaf characteristics are not only widely used to differentiate genera and species (Choi et al, 2020a; Kandemir et al, 2019; Rudall, 1986), but have also been applied in phylogeny for resolving the relationships in several lineages (Rudall, 1994; Wilson, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The micro-morphological data of lemma and palea features of Lolium species Tabaripour et al (2022) showed that more similarity is evident between L. multiflorum and L. perenne. A close similarity was recorded for leaf anatomical structure of L. persicum and L. rigidum (Keshavarzi et al 2014) and by lemma and palea micro-morphological study (Tabaripour et al 2022) that agree with the findings of present study of culm and glume anatomy. In result we pointed to the scattering of L. perenne populations same pattern was present in molecular findings of Tabaripour et al (2021).…”
Section: Discussionmentioning
confidence: 95%
“…Compared with light microscopy, SEM has higher resolution, greater magnification, and more realistic three‐dimensional images. Therefore, they are widely used in the field of botanic research (Ayaz et al, 2020; Jehanzeb et al, 2020; Shah et al, 2019; Tabaripour et al, 2021; Ullah et al, 2019; Ullah et al, 2020; Ullah et al, 2021; Zaman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%